PEMASARAN PRODUK GLOBAL: GLOBAL MARKETING VS LOCALIZED MARKETING - - Cindy (Kompetensi (Competence : Journal of Management Studies), 2015)
Within cross country product marketing, a company had to choose between two of marketing options available, a globalized marketing or marketing using local contents, the glocalized marketing. Both of those methods have its own upsides and downsides as well, a globalized method would be benefitted from the using of one global platform that would be able to used globally using the same core values, but quite often the message would be misinterpreted by the target market because the audience failed to recognize the figures and the values shown within it. Glocalized, even if it have the upsides of being able to be closer to the target market and therefore easier to be understood, have their downsides as well. Other than extra cost to develop, they're potentially too emotionally interesting for the target market, hence the audience would be remembering the advertisement itself but ignoring the product that was offered to them. On that note, a glocalized still need a strong concept of the product itself when it was offered to the audience